Pelaksanaan Putusan Eksekusi BANI atas Sengketa Kontrak antara Badan Layanan Umum BP3TI dengan PT. Indonesia Comnets Plus dan Konsorsium NIPRESS : (Studi Putusan BANI Nomor: 927/II/ARB-BANI/2017) - Pitaloka, Wening Galih; Wardani, Susilo (Ajudikasi : Jurnal Ilmu Hukum, 2023)
The Indonesian National Arbitration Board (BANI) is an option in resolving contract disputes between the government and private parties. When the government is in a losing position in a contract dispute according to the BANI decision, the government must comply with the BANI decision. This study aims to understand the implementation of the execution of BANI decisions that conflict with Law Number 1 of 2004 concerning State Treasury and the authority of the Supreme Court to address the issue of BANI decisions that conflict with Law Number 1 of 2004 concerning State Treasury. The focus of this research includes the execution of BANI decisions that are contrary to Law Number 1 of 2004 concerning State Treasury and the Authority of the Supreme Court to the Court that confiscates state assets. The research method used in this research is normative juridical through statutory and conceptual approaches using secondary legal data consisting of primary legal materials, secondary legal materials and tertiary legal materials. The data obtained from library research is then analyzed using descriptive qualitative. Based on the research, it is found that the execution of the BANI decision carried out by the court through the confiscation of a sum of money in an account belonging to the BP3TI Public Service Agency should not be carried out because this has contradicted Article 50 of Law Number 1 of 2004 concerning State Treasury. Therefore, the Supreme Court is expected to play a role in providing solutions by providing guidance to the lower courts including the district courts by issuing a Supreme Court Circular Letter (SEMA).